Imitation of Children's Speech Styles in The Show "Anomaly" Among Elementary School-Aged Children in Cijoho Village, Kuningan Regency - Sherly Mustikawati; Sri Wulandari; Welly Wihayati (Siber Nusantara of Law and Politic Review, 2026)
Digital media and the use of YouTube, specifically YouTube with its short video content, has had an influence on communication among children who are at the elementary age level. Content that is viewed extensively digitally may potentially affect how children speak due to imitation. The purpose of this research is to determine the reasons behind why children imitate the speech patterns from the “Anomali” series on YouTube, how the imitation process happens, and the effects of imitation on children's communication behavior. Qualitative methods are applied in conducting this study using descriptive methods. Methods used to collect data include observation, in-depth interview, and documentation. Informants for this study include children at the elementary age level and their parents as key informants, along with the child psychologist as a supporting informant. Purposive sampling was the procedure employed for the selection of informants, while triangulation was done for the verification of data. It can be seen that imitation of speech pattern of “Anomali” comes about due to the special characteristics of the characters and their humorous speaking manner. Imitation takes place in the phases of attention, retention, reproduction of verbal behavior, and motivation, according to Dale H. Schunk's theory of social cognitive learning. There are two sides to the effects of imitation: while it offers some advantages like building up one's vocabulary and becoming more confident in communicating, there is also a risk of using language that is not appropriate to the situation without proper guidance from the parents.